Ecological Intelligence in Local Wisdom of The Tengger Tribe as Learning Sources of Social Studies - Ali Sunarno; Nana Supriatna (PAEDAGOGIA, 2023)
The Tengger tribe has local wisdom as a form of ecological intelligence in minimizing natural damage. Local wisdom is important to be bequeathed to the next generation, but the current globalization hampers the process of inheriting these values. Education, in this case, Social Studies subjects, is heavily responsible for internalizing these noble values. This article was written based on the results of a qualitative descriptive study that explored the potential of the local wisdom of the Tengger people related to ecological intelligence. Based on the research results, the people of the Tengger Tribe have wisdom in managing land, forests/trees, and water. Local wisdom, a form of ecological intelligence, can be adopted as a Social Studies learning resource in junior high schools in the Merdeka Curriculum. The research results are expected to be used as a reference in developing Social Studies learning based on local culture.